PERSON-JOB-AND ORGANIZATION FIT DURING THE COVID-19 PANDEMIC AND THE IMPACT ON EMPLOYEE SATISFACTION AND PERFORMANCE - Widyawati, Sapta Rini; Widnyana, I Wayan; Da Costa, Carla Alexandra De Jesus (Universitas Muria Kudus, 2025)
This paper discusses person-job-fit (PJF) and person-organization-fit (POF) during the Covid-19 pandemic, and their impact on employee satisfaction and performance. The data was obtained from the distribution of electronic questionnaires to employees working in Indonesia. Data analysis using path analysis model. The results show that PJF and POF during the Covid-19 pandemic were quite good, even though the environment had forced them to work with a new system, namely work from home. In addition, PJF proved to be positively and significantly associated with job satisfaction, but not significant with performance. While the POF proved to be positively and significantly related to satisfaction and performance. Thus, this study failed to prove a mediating effect of satisfaction on the relationship between PJF and POF with performance. When compared between the two, POF has a greater role than PJF in explaining job satisfaction.